Income distribution among those of 65 years and older in Sweden - Gabriella Sjögren Lindquist; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2012)
The population of Sweden is ageing and the number of pensioners is increasing. This means that the incomes of older people and the income differences between older and younger people and among pensioners have become more important in terms of public debate and research. In this paper, we examine the income distribution of those 65 years and older. The income differences among both men and women have increased among those of 65-74 years and older since 1982. Women generally have lower incomes and pensions than men. Foreign born persons generally have lower incomes and pensions compared to natives. This difference has increased, especially with regard to those coming from non-OECD countries. Among those with low pensions, women, the foreign born and those who have been self-employed are overrepresented. Many who retire have large amount of net wealth, especially in the form of property (houses, apartments).
Keywords: J14; D31; H55; 330; older workers; retirement; pension; income inequality; Alte Menschen; Einkommensverteilung; Altersgrenze; Schweden